Fish Embryo Acute Toxicity Testing and the RTgill‐W1 Cell Line as In Vitro Models for Whole‐Effluent Toxicity (WET) Testing: An In Vitro/In Vivo Comparison of Chemicals Relevant for WET Testing. (23rd September 2022) - Scott, Justin; Grewe, Ryan; Minghetti, Matteo
Abstract: The fathead minnow ( Pimephales promelas ) fish embryo acute toxicity (FET) test was compared to the fish gill cells (RTgill‐W1) in vitro assay and to the fish larvae acute toxicity test to evaluate their sensitivity for whole‐effluent toxicity (WET) testing. The toxicity of 12 chemicals relevant for WET testing was compared as proof of principle. The concentrations lethal to 50% of a population (LC50) of embryos were compared to those in fish larvae and to the 50% effect concentration (EC50) in RTgill‐W1 cells from previous literature. Along with traditional FET endpoints (coagulation, somite development, tail detachment, and heartbeat), cardiotoxicity was evaluated for WET applicability. Heart rate was measured at LC20 and LC50 values of six subselected chemicals (Cd, Cu, Ni, ammonia, 3, 4‐dichloraniline, and benzalkonium chloride). In addition, the toxicity of Cd and Ni was evaluated in RTgill‐W1 cells exposed in a hypoosmotic medium to evaluate the effect that osmolarity may have on metal toxicity. A significant correlation was found between the FET and larvae LC50 values but not between the RTgill‐W1 EC50 and FET LC50 values. Although sensitivity to Ni and Cd was found to increase with hypoosmotic conditions for FET and RTgill‐W1 cells, a correlation was only found with removal of Ni from the analysis. Hypoosmotic conditions increased sensitivity with a significant correlation between RTgill‐W1 cells and larvae. Cardiotoxicity was shown in three of the five subselected chemicals (Cd, Cu, and 3, 4‐dichloroaniline). Overall, both in vitro alternative models have shown good predictability of toxicity in fish in vivo for WET chemicals of interest. Environ Toxicol Chem 2022;41:2721–2731. © 2022 SETAC